DSS Approach with the AHP Method in the Selection of Quiz Participants at SDIT Permata Cendekia - Ahmad Fadhli Hasibuan; Rahmat W. Sembiring; Muhammad Ridwan Lubis (Yayasan Literasi Sains Indonesia, 2023)
This study aims to develop a decision support system for the selection of intelligent candidates using the Analytical Hierarchy Process (AHP) method. The case study was conducted at SDIT Permata Cendekia, an educational institution in Indonesia. The AHP method is used as a framework for making decisions based on hierarchically determined criteria and sub-criteria. The data needed in this study were obtained through interviews and observations at SDIT Permata Cendekia. After that, the steps in the AHP method, namely making a pairwise comparison matrix, calculating the weight of criteria and sub-criteria, and calculating alternative scores, are carried out in developing a decision support system. Based on the research, it was found that alternative A3 was the best alternative out of 12 alternatives assessed based on 4 (four) assessment criteria. This research is expected to be able to provide effective and efficient solutions in the process of selecting candidate quizzes at SDIT Permata Cendekia, as well as being the basis for developing a similar decision support system in selecting candidate quizzes at other educational institutions.